Management information system: for bba fourth semester of wbut - Jindal, Aman (Kalyani Pub, 2011)
Management information system: for bba fourth semester of wbut / Jindal, Aman. -- Kolkata: Kalyani Pub., 2011 658.4038011 J61e2 2nd rev. ed. No. of Copies : 1